Leclercia adecarboxylata Bacteremia in a Patient with Ulcerative Colitis - Amir Kashani; Morteza Chitsazan; Kendrick Che; Roger C. Garrison (Case Reports in Gastrointestinal Medicine)
Patients with inflammatory bowel disease (IBD) are a high risk population for bacteremia. Derangement in the mucosal architecture of the gastrointestinal (GI) tract and frequent endoscopic interventions in immunocompromised individuals are considered primary causes. Isolation of opportunistic microorganisms from the bloodstream of IBD patients has been increasingly reported in recent years. Leclercia adecarboxylata is a ubiquitous, aerobic, motile, gram-negative bacillus. The human GI tract is known to harbor this rarely pathogenic microorganism. There are only a few case reports of bacteremia with this microorganism; the majority are either polymicrobial or associated with immunocompromised patients. We describe a case of monomicrobial L. adecarboxylata bacteremia in a 43-year-old female who presented with bloody diarrhea. Colonoscopy revealed diffuse colonic mucosal inflammation with numerous ulcers, and histopathology revealed crypt abscesses. Following an episode of rectal bleeding, two sets of blood cultures grew L. adecarboxylata, which was treated with intravenous ceftriaxone. After a complicated hospital course, she was eventually diagnosed with ulcerative colitis and enteropathic arthritis, treated with intravenous methylprednisolone, mesalamine, and infliximab which resulted in resolution of her symptoms. In our previously immunocompetent patient, derangement of the gut mucosal barrier was the likely cause of bacteremia, yet performing endoscopic intervention may have contributed to bacterial translocation.